Preference Analysis Of Traditional Traders Towards Relocation Of The Deli Tua Market In City Structure In The District Of Deli Tua Deli Serdang Regency - Feby Kartika, Sarah; Sirojuzilam, Sirojuzilam; Purwoko, Agus (Publisher Cv. Inara, 2022)
The purpose of this study was to analyze the effect of new market characteristics (tariffs, potential traders, facilities, access, merchandise diversity) on the preferences of traders in Deli Tua District, Deli Serdang Regency; analyze the effect of the old market characteristics (tariffs, potential traders, facilities, access, merchandise diversity) on the preferences of traders in Deli Tua District, Deli Serdang Regency; and to analyze the effect of market relocation on urban planning in Deli Tua District, Deli Serdang Regency. With a total sample of 72 traders from a total of 245 population. The analytical method used in this research is multiple regression analysis. The results obtained are: 1) Partially the characteristics of the new market in the form of tariffs have a positive and significant effect, potential buyers have a negative and significant effect, facilities have a positive and insignificant effect, access has a negative and significant effect, and merchandise diversity has a positive and significant effect on the preferences of market traders. new. Simultaneously the characteristics of the new market have a positive and significant effect on the preferences of new market traders; 2) Partially, the characteristics of the old market in the form of tariffs have a positive and insignificant effect, potential buyers have a positive and significant effect, facilities have a positive and significant effect, access has a positive and significant effect, and trade diversity has a positive and significant effect on the preferences of old market traders. Simultaneously, the characteristics of the old market have a positive and significant effect on the preferences of the old market traders; 3) The relocation of the old market from the Old Deli Traditional Market to the Traditional-Modern Deli Old Town has not yet had an impact on a better urban arrangement because the old market is still operating, traffic jams still occur and are still irregular.